ANALISA VARIASI UKURAN RUNNER SYSTEM DAN MELT TEMPERATURE TERHADAP FILL TIME, CONFIDENCE OF FILL DAN QUALITY PREDICTION - Ellianto, Mario Sariski Dwi; Wibowo, Midarto Dwi; Wirakusuma, Kadex Widhy (Otopro, 2025)
The technology used in making plastic products is injection molding technology. In general, the products obtained are notof good quality, so simulations need to be carried out to determine the correct production process parameters. This research focuseson determining the effect of variations in runner system size and variations in melt temperature on the optimal fill time, confidence offill, and quality prediction for tensile test specimen products. This research uses a simulation approach with the help of software. Thesimulation method is used to determine the characteristics of each variation in runner size and melt temperature. The type of runnerlayout used is a grid layout type, the runner system type is H balance, and the cross-section type is circle-shaped. Variations in runnersize use runner diameters of 2 mm, 3 mm, and 4 mm. Variations in melt temperature use values of 190°C, 200°C, and 210°C. Thesimulations carried out include fill time analysis, confidence of fill analysis, and quality prediction analysis. Simulation results of filltime, confidence of fill and quality prediction at a runner diameter of 2 mm and melt temperature of 210°C yielded optimal values of0.7524 s, 100% and 95.1%, respectively. These conditions ensured that the molten polymer remained in a fully flowable state untilcomplete cavity filling was achieved, thereby minimizing the risk of defects and enhancing cycle time efficiency. An increase in runnersize results in reduced flow resistance of the molten material, while the melt temperature remains within the process conditionsrecommended by the material manufacturer.